Physical Characteristics of Section Coal and Rock Pillars Under Roof Shock Disturbances From Goaf - Su, Ronghua; Shen, Hongshuang (Frontiers in Physics, 2020)
The stability of rock strata structure is closely related to its response physical characteristics under external shock disturbance. The roof shock disturbance from goaf is usually one of the important factors of causing coal and rock pillars instability. It is necessary to study the dynamic physical characteristics of coal and rock pillars under roof shock disturbance from goaf. The dynamic structural system model of elastic-plastic finite element was established for the formation of surrounding rock and coal pillars in a deep stope. And the response physical characteristics of coal pillars with different widths were analyzed, under the roof shock disturbance intensity and frequency from goaf. The natural vibration characteristics of the stope model were calculated and the first ten orders natural frequencies were extracted. Calculations indicated that the vertical displacement and the plastic zone occupation ratio of the coal pillar increased with the increase of the shock disturbance intensity, decreased with the increase of the shock disturbance frequency, and decreased with the increase of the coal pillar width. The influence of the vertical deformation and the plastic zone occupation ratio of the coal pillar under shock disturbance frequency was more obvious compared with that of shock disturbance intensity, especially at low frequency. The closer the shock disturbance frequency was to the natural frequency of the model, the larger the plastic zone of coal pillars was, which the bearing capacity of coal pillar decreased significantly. It is significant that more attention should be paied to monitoring the frequency of roof shock disturbance signal when design coal pillars width in the coal mine.